Preparation of REE-doped NaY(WO4)2 single crystals for quantitative determination of rare earth elements in REE:NaY(WO4)2 laser crystals by LA-ICP-MS. Issue 41 (6th October 2022) - Zhang, Yu; Sun, Yijian; Zhou, Jianzong; Yang, Jian; Deng, Jun; Shao, Jianfeng; Zheng, Tengfei; Ke, Yuqiu; Long, Tao
Abstract : An analytical method for quantitative determination of REE concentration in NaY(WO4 )2 laser crystals by LA-ICP-MS was proposed using a synthetic REE-doped NaY(WO4 )2 single crystal NaYW-500 as an external calibrator. Abstract : In REE:NaY(WO4 )2 laser crystals, optical properties like laser conversion efficiency are dependent on the doped rare earth element (REE) concentration, which necessitates the importance for accurate determination of the REE concentration in these precious samples. However, in situ microanalysis of these samples by laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS) is often hampered by the lack of matrix-matched reference materials. In this work, a REE-doped NaY(WO4 )2 single crystal (NaYW-500) that has a nominal REE concentration of 500 μg g −1 was synthesized and employed as a candidate reference material. Its homogeneity (1 RSD of elemental concentration or 89 Y-normalized signal intensity) was measured by electron probe microanalysis (EPMA) and LA-ICP-MS to be less than 2% for major elements and mainly <3% for REEs, respectively. Then, an LA-ICP-MS analytical method was developed by using 89 Y as the internal standard and using NaYW-500 as the external calibrator under the optimal operating conditions. Quantitative determination of the REE concentration in the other two REE:NaY(WO4 )2 single crystals NaYW-50 and NaYW-5000 show that these samples can be accurately measured with relative deviations ( D r ) of −6.00 to 12.33% and −9.86 to 6.94%, respectively. Further application of the proposed analytical method to quantitative determination of the Ho concentration in a Ho:NaY(WO4 )2 laser crystal shows that desirable accuracy was obtained with a D r of 4.62%. It demonstrates that the proposed method by preparing REE-doped NaY(WO4 )2 single crystals for quantitative determination of the REE concentration in NaY(WO4 )2 laser crystals is valid and robust.